2010
DOI: 10.3390/molecules15042139
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Antioxidant Capacity and Cytotoxicity of Selected Malaysian Plants

Abstract: Thirteen Malaysian plants; Artocarpus champeden, Azadirachta indica, Fragaria x ananassa, Garcinia mangostana, Lawsonia inermis, Mangifera indica, Nephelium lappaceum, Nephelium mutobile, Peltophorum pterocarpum, Psidium guajava and Syzygium aqueum, selected for their use in traditional medicine, were subjected to a variety of assays. Antioxidant capability, total phenolic content, elemental composition, as well as it cytotoxity to several cell lines of the aqueous and ethanolic extracts from different parts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 20 publications
4
49
1
1
Order By: Relevance
“…It is found that antioxidant activity of S. caryophyllatum extracts increased proportionally to the polyphenol content with a linear relationship between DPPH values and total polyphenols 39 . The results here reported for DPPH radical scavenging are comparables and in accordance with those reported by some authors for some syzygium species extracts (S. jambolana, S. cumini, S. aqueum, S. grantum) for DPPH and other radical scavenging [40][41][42][43][44][45][46][47] . From this study, it can be inferred that S. caryophyllaum and S. densiflorum are also equally having antioxidant proprieties.…”
Section: Dpph Radical Scavenging Activitysupporting
confidence: 94%
“…It is found that antioxidant activity of S. caryophyllatum extracts increased proportionally to the polyphenol content with a linear relationship between DPPH values and total polyphenols 39 . The results here reported for DPPH radical scavenging are comparables and in accordance with those reported by some authors for some syzygium species extracts (S. jambolana, S. cumini, S. aqueum, S. grantum) for DPPH and other radical scavenging [40][41][42][43][44][45][46][47] . From this study, it can be inferred that S. caryophyllaum and S. densiflorum are also equally having antioxidant proprieties.…”
Section: Dpph Radical Scavenging Activitysupporting
confidence: 94%
“…Inhibition of lipid peroxidation as exhibited by Garcinia mongostana [54], Alstonia scholaris [55,56] and Annona muricata [49,57,58]. 2.…”
Section: Resultsmentioning
confidence: 99%
“…3. Inhibiting proliferation via the activation of caspase-3 and caspase-9, up-regulation of the ratio of bax/bcl-2 protein expression in Ardisia brevicaulis [61] Artocarpus obtusus [50,62] Ardisia brecaulis [63], Carica papaya [64] Catharanthus roseus [118][119], Costus speciosus [121][122], Cucuma zedoaria [65], Dysoxylum cauliforum [66], Goniosthalamus macrophyllus [137][138], Gynura procumbens [139], Lawsonia inermis [56,[146][147], Leea indica [148][149], Nepthelium lappaceum [56,156] Pandanus amarylfolius [41], Phyla nodiflora [67], Physalis minima [52,78], Rhodiola rosea [68], Vernonia amygdalina [65] and Schima wallichi [38]. 4.…”
Section: Resultsmentioning
confidence: 99%
“…The increasing market demand for rambutan will also increase its waste because rambutan peel is still considered as waste and has never been used yet. Peel of rambutan has a potential as an afford able herbal medicine due to its phytochemical compounds (Ling et al, 2010;Wulandari and Lestari, 2012). Identification tannins compounds by TLC, B HPLC chromatograms, peak 1 is ellagic acid, peak 2 is coraligiin and peak 3 is geraniin, C FT-IR interpretation RPE fuctional bunch…”
Section: Distribution and Yield Potencies Of Local Rambutanmentioning
confidence: 99%